Psychological Effects of the COVID-19-Induced Lockdown 2020 among Educated Adults of Nepal: Array - Adhikari, Pralhad (New Trends in Psychology, 2020)
Using diary method, a qualitative research was conducted to know about the feelings, actions and mental processes of the adults during lockdown induced by COVID-19 in 2020. The final dataset had 1800 entries from 30 participants for 20 days during May and June months of 2020. The participants were made write diary in MS Word file with a ‘change tracker’ on. The sampling was non-probability, convenient. NVivo 10 was used to analyze the data. Data have been collected phenomenologically and have been analyzed by content analysis. Consequently, three themes in emotions were found out: positive emotions, negative emotions and mood swing. Behaviors had three themes: adaptation, entertainment and compulsive behaviors. Mental processes had three themes: attribution, acceptance and cognition. The conclusion is that people have started to adapt to new norms created by the lockdown of COVID-19. Still, they are afraid/anxious about start and spread of disease as they have an obsession. In response, they show compulsive behaviors like seeking news. They think that government is responsible for the proper handling of crisis. They are angry at people for being careless when they often break the lockdown themselves.